SIMULATED CHANGE: TOTALITARIANISM AND WHAT COMES NEXT. - Cristina Petrescu, Cristina Petrescu (Porównania, 2019)
My intervention focuses on Aviezer Tucker’s assessment of legacies of totalitarianism in the educational system. Tucker singles out a major dilemma of post-totalitarian universities: to fundamentally restructure in order to become autonomous or to simulate change while preserving state support. He contends that the Bologna system meant the transformation of universities into state-managed corporations that lowered standards and introduced various mechanisms of measuring performance. Thus, Tucker convincingly argues, the unwanted result of including the former communist coun-tries in the European Union was the return to a familiar model of simulated change in the field of education.